Method for preparing super-early-strength micro-expansion roadbed grouting material from CFB ash
By screening and preparing grouting materials for CFB ash and blast furnace slag that meet the requirements, the problems of low utilization of CFB ash and easy shrinkage of grouting materials are solved, and the preparation of ultra-prematurely strong micro-expanded subgrade grouting materials are realized, which improves the roadbed repair effect and the utilization rate of CFB ash.
Patent Information
- Application Number
- CN202510088561.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
The CFB ash utilization rate is low, and the prepared roadbed grouting materials are prone to shrink, resulting in low strength and unstableness.
The grouting material was formed by screening CFB ash and blast furnace slag that meets the particle size and unstable component content requirements, and preparing alkali triggers. The method includes the combination of CFB ash, blast furnace slag, alkali trigger, water reducer and water, and controls the water-solid ratio between 0.63 and 0.75.
The ultra-premature strong micro-expanded subgrade grouting material was successfully prepared, which improved the utilization rate of CFB ash, reduced the use of cement-type high-energy-consuming products, and improved the effect of subgrade grouting repair.
Smart Images

Figure CN119822707A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and in particular relates to a method for preparing an ultra-early strength micro-expansion roadbed grouting material using CFB ash. Background Art
[0002] Fly ash is a byproduct of the production process of thermal power enterprises. According to the type of boiler, it can be divided into pulverized coal furnace source fly ash (PCFA) and circulating fluidized bed boiler source fly ash (CFB ash). Circulating fluidized bed boilers have multiple advantages over pulverized coal boilers: high combustion efficiency (97.5-99.5%), low combustion temperature (850-900℃), less atmospheric pollutants (SO 2 and NOx), wide applicability (including domestic waste, industrial sludge, low-quality coal, coal gangue, etc.) and a wide range of fuel particle size (0-10mm). Therefore, circulating fluidized bed boilers are widely used in thermal power enterprises. However, with the popularization of circulating fluidized bed boilers, the emission of its by-product CFB ash continues to increase. It is estimated that China's annual emissions exceed 280 million tons, the United States and Europe are 14 million tons and 1.5 million tons respectively. However, the comprehensive utilization rate of CFB ash is less than 20%, and most of the CFB ash is piled up and landfilled, which not only occupies a large amount of farmland, but also may cause geological disasters and environmental pollution, seriously affecting the ecological environment. Therefore, the effective recycling and utilization of CFB ash is crucial to environmental protection and promoting the sustainable development of thermal power enterprises.
[0003] In terms of microstructure, CFB ash exhibits irregular and porous characteristics. The combustion temperature of circulating fluidized bed boiler is relatively low (about 1200-1400℃), which makes it difficult for clay minerals to form a glass phase, resulting in low reactivity. In terms of chemical composition, CFB ash generally contains high levels of CaO and SO 3 , as well as unstable free calcium oxide (f-CaO) and SO 3 These differences are mainly due to the addition of desulfurizers such as limestone during combustion in circulating fluidized bed boilers. In summary, CFB ash has low activity and unstable components (such as f-CaO and SO 3 ) results in the prepared geopolymer material having low strength and prone to volume expansion problems, which limits the application of CFB ash in construction projects.
[0004] In recent years, the daily traffic volume of my country's highways has increased rapidly. During the high load and long service time, the roads are prone to various diseases such as roadbed debonding and loosening. If not handled in time, these diseases will further cause road subsidence, potholes, cracks and other quality defects, seriously affecting the service life of the road and driving safety. Trenchless grouting technology has the advantages of convenient construction, no need to close traffic for a long time, and little interference with traffic, and has become a popular technology for trenchless repair of roadbed. Grouting materials are the main body of trenchless grouting. At present, cement-based grouting materials are the most widely used, but their defects such as long setting time, poor fluidity, and low early strength growth rate are becoming increasingly prominent. With the increase of social environmental awareness, environmental problems such as non-renewable raw materials for cement preparation, high energy consumption in the preparation process, and heavy pollution are also becoming more and more apparent. The research and development of chemical slurries has solved engineering problems such as reinforcement, anti-seepage, and plugging under complex conditions to a certain extent, but their high cost, difficult transportation, poor applicability, and environmental pollution make chemical slurries difficult to use on a large scale in grouting projects. With the promotion of carbon neutrality, it is particularly important to solve practical engineering problems while ensuring energy conservation, emission reduction and environmental protection. The development of green, environmentally friendly, low-energy high-performance slurry is the development trend of grouting materials.
[0005] Geopolymers and cement-based grouting materials often shrink during the strength building process, which can cause gaps in the filled areas. These gaps in the roadbed are prone to water seepage, and under the action of vehicle loads, the gaps will further expand, causing water damage, affecting the roadbed stiffness and driving safety.
[0006] Therefore, there is an urgent need for a simple and effective method for preparing roadbed grouting materials to prepare micro-expanding grouting materials while improving the utilization rate of CFB ash. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash, so as to solve the problems of low utilization rate of CFB ash and easy shrinkage of the prepared roadbed grouting material.
[0008] The technical solution adopted by the present invention is:
[0009] The method for preparing ultra-early strength micro-expansion roadbed grouting material using CFB ash comprises the following steps:
[0010] S1: Screening CFB ash and blast furnace slag that meet the requirements of particle size and unstable component content;
[0011] S2: prepare alkali activator;
[0012] S3: Take CFB ash and blast furnace slag, stir the CFB ash and blast furnace slag, add alkali activator, water reducing agent and water to form grouting material.
[0013] Furthermore, in said S1,
[0014] The particle size requirements of CFB ash are: median particle size D 50 ≤70μm.
[0015] Furthermore, in said S1,
[0016] The particle size requirements of blast furnace slag are: median particle size D 50 ≤12μm.
[0017] Furthermore, in said S1,
[0018] In CFB ash, the unstable components are f-CaO and SO 3 ;
[0019] The mass percentage of f-CaO is controlled at 1% to 4%, and SO 3 The mass percentage is between 2.5% and 4.5%.
[0020] Furthermore, in S2,
[0021] Use water glass to prepare the alkali activator;
[0022] The modulus range of water glass is 1.1M~2.2M.
[0023] Furthermore, in S2,
[0024] The modulus of the alkali activator is controlled at 0.9M~1.1M.
[0025] Furthermore, in S3,
[0026] The mass fraction of CFB ash is 60-75 parts, the mass fraction of blast furnace slag is 25-40 parts, the mass fraction of alkali activator is 30-40 parts, the mass fraction of water reducer is 1-2 parts, and the water-solid ratio is 0.63-0.75.
[0027] Furthermore, in S3,
[0028] When 60 parts ≤ CFB ash parts ≤ 65 parts, the water-solid ratio is controlled at 0.63-0.75;
[0029] When 65 parts < CFB ash content ≤ 70 parts, the water-solid ratio is controlled at 0.63-0.70;
[0030] When 70 parts < CFB ash content ≤ 75 parts, the water-solid ratio is controlled at 0.65-0.68.
[0031] The beneficial effects of the present invention are
[0032] 1. The shrinkage of grouting materials will have an adverse effect on the grouting repair effect. The unstable components f-CaO and SO in CFB ash 3 This will result in the geopolymer material produced being of low strength and prone to volume shrinkage. The present invention utilizes this characteristic to successfully produce micro-expansion grouting materials, turning disadvantages into advantages and turning waste into treasure.
[0033] 2. The present invention provides a new recycling method for CFB ash, which can consume a large amount of CFB ash; at the same time, the roadbed grouting material produced has the characteristics of ultra-early strength and micro-expansion, which not only reduces the use of cement-based high-energy consumption products, but also improves the effect of roadbed grouting repair.
[0034] 3. The prepared roadbed grouting material can be hardened and formed in 3 days, and its strength in 7 days meets the requirements of roadbed grouting specifications.
[0035] 4. Compared with cement grouting materials, the present invention greatly shortens the strength formation period of the grouting materials and reduces the road closure time. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 Graph showing particle size distribution of CFB ash and blast furnace slag of the present invention.
[0038] Figure 2 are SEM images of precursor materials, where a is the SEM image of CFB ash and b is the SEM image of blast furnace slag.
[0039] Figure 3 It is a comparison chart of the fluidity of grouting materials prepared with different water-solid ratios at different CFB ash content.
[0040] Figure 4 It is a comparison chart of the initial setting time of grouting materials prepared with different water-solid ratios at different CFB ash content.
[0041] Figure 5 It is a comparison chart of the final setting time of grouting materials prepared with different water-solid ratios at different CFB ash dosages.
[0042] Figure 6 It is a comparison chart of water separation rate of grouting materials prepared with different water-solid ratios at different CFB ash dosages.
[0043] Figure 7It is a comparison chart of the 3D compressive strength of grouting materials prepared with different water-solid ratios at different CFB ash content.
[0044] Figure 8 This is a comparison chart of the 7d compressive strength of grouting materials prepared with different water-solid ratios and different CFB ash content.
[0045] Fig. 9 This is a comparison chart of the 28d compressive strength of grouting materials prepared with different water-solid ratios and different CFB ash content.
[0046] Fig.10 It is a comparison chart of the expansion rates of grouting materials prepared at different water-solid ratios at different CFB ash dosages. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The complete steps of the embodiment of the present invention are as follows:
[0049] S1: Select the formation temperature and size of the solid waste material. The solid waste material includes CFB ash and blast furnace slag.
[0050] See also Figure 1 , CFB ash particle size requires a median particle size D 50 ≤70μm, D 50 ≤70μm is to ensure that 50% of all particle sizes are within 70μm. Particle size is a key parameter that determines the reactivity. The smaller the particle size, the higher the activity. This selection is to ensure the reactivity of CFB ash. 50 ≤70μm ensures that at least 50% of the CFB ash has high reactivity, D 50 >70μm, the strength and micro-expansion results of the grouting material are likely to be seriously affected; while D 50 ≤70μm can be met by most CFB ashes and can be used directly without further processing; 850℃≤CFB ash formation temperature≤900℃. Temperature is also a decisive factor in reaction activity. Temperature below 850℃ may result in: slow strength development or even substandard strength; at the same time, there is no expansion effect, or the expansion effect turns into contraction.
[0051] f-CaO content is 1% to 4%, SO 3 The content is 2.5% to 4.5%;
[0052] Blast furnace slag particle size requirements median particle size D 50 ≤12μm, 1200℃≤blast furnace slag formation temperature≤1400℃; particle size and temperature requirements are to ensure that the material has a certain reactivity;
[0053] Table 1 shows the selected products that meet the requirements of f-CaO, SO 3 The main chemical components of CFB ash and blast furnace slag, the data units in the table are: wt.%,
[0054] Table 1 Main chemical compositions of CFB ash and blast furnace slag (wt.%).
[0055]
[0056]
[0057] The SEM images of the precursor materials are shown in Figure 2 As shown, a is the SEM image of CFB ash, and b is the SEM image of blast furnace slag.
[0058] S2: Alkaline activators can provide a sufficient alkaline environment to cause the active components in the mineral material to undergo hydration reactions and generate products with gelling properties. Common alkaline activators include water glass and sodium hydroxide, which can better activate mineral materials;
[0059] When configuring the alkali activator, select a water glass modulus greater than 1.1M, ranging from 1.1M to 2.2M. The smaller the difference between the water glass modulus and the alkali activator modulus, the less sodium hydroxide is added. The alkali activator is prepared by adding flake sodium hydroxide (for easy reaction), and the alkali activator modulus is controlled at 0.9M to 1.1M. Too large or too small will lead to low strength, or even very low strength, which cannot meet the requirements. The prepared alkali activator is aged in a closed container for 16 to 30 hours (so that the sodium hydroxide is fully dissolved in the water glass, and the aged alkali activator is clear and transparent).
[0060] Control the dosage of alkali activator and water-solid ratio. The dosage of alkali activator should be controlled at 30% to 40%. Too much alkali activator dosage will lead to excessive alkali (excess alkali), while too little alkali activator dosage will lead to incomplete dissolution of silicon oxide, aluminum oxide and calcium oxide in CFB and GGBS, and they will not be able to participate in the reaction to the maximum extent, affecting the strength and expansion.
[0061] S3: Take 60-75 parts of CFB ash, because the reactivity of CFB is not as good as that of blast furnace slag (GGBS), that is, the geopolymer grouting material prepared with CFB alone has no strength. Too small a portion of CFB will result in the setting time not meeting the requirements, CFB has a retarding effect, too large a portion of CFB will result in low strength of the prepared material, slow strength development, and not meeting the requirements; 25-40 parts of blast furnace slag, 30-40 parts of alkali activator, 1-2 parts of water reducer, too large a portion of water reducer will affect the setting time, too small a portion will result in fluidity not meeting the requirements; add 40-55 parts of additional water (considering the water brought by the alkali activator);
[0062] When 60 parts ≤ CFB ash parts ≤ 65 parts, the water-solid ratio is controlled at 0.63-0.75;
[0063] When 65 parts < CFB ash content ≤ 70 parts, the water-solid ratio is controlled at 0.63-0.70;
[0064] When 70 parts < CFB ash content ≤ 75 parts, the water-solid ratio is controlled at 0.65-0.68;
[0065] First, stir the CFB ash and blast furnace slag for 5 to 8 minutes until they are uniform, then add the weighed water reducer, alkali activator and water, and immediately stir quickly for 2 to 5 minutes to ensure that there are no lumps of solids and form a uniform grouting material;
[0066] Through microscopic mechanism analysis, it is proved that the expansion does not affect its durability, ensuring the preparation of high-performance grouting materials.
[0067] Example 1: 60 parts of CFB ash, 40 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, water reducer 1 part.
[0068] Example 2: 60 parts of CFB ash, 40 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.70, water reducer 1 part.
[0069] Example 3: 60 parts of CFB ash, 40 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.75, water reducer 1 part.
[0070] Example 4: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, water reducer 1 part.
[0071] Example 5: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.70, and water reducer 1 part.
[0072] Example 6: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.75, water reducer 1 part.
[0073] Example 7: 70 parts of CFB ash, 30 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1 part.
[0074] Example 8: 70 parts of CFB ash, 30 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.70, and water reducer 1 part.
[0075] Example 9: 75 parts of CFB ash, 25 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1 part.
[0076] Example 10: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, water reducer 1.5 parts.
[0077] Example 11: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 0.9, alkali activator dosage 30%, water-solid ratio 0.63, water reducer 1.5 parts.
[0078] Example 12: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 1.1, alkali activator dosage 40%, water-solid ratio 0.65, and water reducer 2 parts.
[0079] Example 13: 70 parts of CFB ash, 30 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.63, and water reducer 1 part.
[0080] Example 14: 75 parts of CFB ash, 25 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.68, and water reducer 1 part.
[0081] Example 15: 72 parts of CFB ash, 28 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1 part.
[0082] Comparative Example 1: 60 parts of CFB ash, 40 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.60, and water reducer 1 part.
[0083] Comparative Example 2: 65 parts of CFB ash, 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.60, and water reducer 1 part.
[0084] Comparative Example 3: 70 parts of CFB ash, 30 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.60, and water reducer 1 part.
[0085] Comparative Example 4: 70 parts of CFB ash, 30 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.75, and water reducer 1 part.
[0086] Comparative Example 5: 75 parts of CFB ash, 25 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.60, and water reducer 1 part.
[0087] Comparative Example 6: 75 parts of CFB ash, 25 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.70, and water reducer 1 part.
[0088] Comparative Example 7: 75 parts of CFB ash, 25 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.75, and water reducer 1 part.
[0089] Comparative Example 8: 80 parts of CFB ash, 20 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.60, and water reducer 1 part.
[0090] Comparative Example 9: 80 parts of CFB ash, 20 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1 part.
[0091] Comparative Example 10: 80 parts of CFB ash, 20 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.70, and water reducer 1 part.
[0092] Comparative Example 11: 80 parts of CFB ash, 20 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.75, and water reducer 1 part.
[0093] Comparative Example 12: 65 parts of fly ash, 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1.5 parts.
[0094] Comparative Example 13: 65 parts of CFB ash, 35 parts of fly ash, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1.5 parts.
[0095] Examples 1-15 and Comparative Examples 1-13 all use the unstable components f-CaO and SO that meet the particle size requirements. 3 Content requirements.
[0096] Comparative Example 14: 65 parts of CFB ash, wherein the median particle size of CFB ash D50>70, which is 110.58 μm; 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, and water reducer 1.5 parts.
[0097] Comparative Example 15: 65 parts of CFB ash, 35 parts of blast furnace slag, wherein D50>12, 18.26 μm; blast furnace slag alkali activator modulus 1.0, alkali activator dosage 35%, water-solid ratio 0.65, water reducer 1.5 parts.
[0098] Comparative Example 16: 65 parts of CFB ash, wherein the f-CaO content is 0.2%, SO 3 The content is 1.1%; 35 parts of blast furnace slag, alkali activator modulus 1.0, alkali activator dosage is 35%, water-solid ratio 0.65, and water reducer is 1.5 parts.
[0099] According to the requirements of the Technical Specification for Geopolymer Grouting Reinforcement of Highway Roadbed and Base (SZ-G-B04-2007), the prepared grouting material requires fluidity ≤17s, initial setting time ≥30min, final setting time ≤400min, 7-day strength ≥2.47MPa, and 28-day strength ≥4.20MPa. According to the requirements of the specification, high-performance grouting materials that meet the requirements of fluidity, setting time and strength are selected.
[0100] The grouting materials prepared in the examples and comparative examples were tested for fluidity, setting time, water separation rate, strength, and expansion performance.
[0101] Table 2 Evaluation indexes of embodiments and comparative examples
[0102]
[0103]
[0104] Among Examples 1-6 and Examples 10-12, Example 10 meets the requirements of the specification on fluidity, setting time and strength at the same time, and has a low water separation rate and a moderate expansion rate, and has the best effect.
[0105] Among Examples 7-8 and 13, Example 7 has the best effect.
[0106] Among Examples 9, 14-15, Example 15 has the best effect.
[0107] Comparative Example 12: After CFB ash was replaced with fly ash, the fluidity of the grouting material increased, the setting time was shortened, and the strength was improved, but its water separation rate increased significantly. The grouting material shrank during the strength formation process, which was not conducive to grouting repair. The reason is that CFB ash has a porous structure that increases water absorption, thereby reducing the water separation rate. The f-CaO and SO in CFB ash 3 It can produce expansion due to reaction, but there is no f-CaO, SO in fly ash. 3 The content is extremely low, resulting in the grouting material no longer having an expansion effect.
[0108] Comparative Example 13 replaces blast furnace slag with fly ash, resulting in reduced fluidity, extended setting time, slightly increased water separation rate, significantly reduced strength, and reduced micro-expansion effect. The reason is that the reaction activity of blast furnace slag is higher than that of fly ash, which slows down the reaction rate, reduces the reaction product (cementitious material), reduces the strength, and at the same time, the f-CaO and SO in CFB ash 3 The amount participating in the reaction is reduced, resulting in less swelling.
[0109] Comparative Examples 14 and 15 have low reactivity due to the particle size not meeting the requirements, so the strength and micro-expansion results of the grouting materials are seriously affected; Comparative Example 16 has unstable components f-CaO and SO 3 If the content is too low, the expansion effect disappears and turns into a contraction effect.
[0110] Figure 2 The following are the microscopic surface SEM images of CFB ash and blast furnace slag, where a is the microscopic surface SEM image of CFB ash and b is the microscopic surface SEM image of blast furnace slag. It can be seen that the microscopic surface of CFB ash is rough and porous, resulting in a higher water absorption rate. In contrast, the microscopic morphology of GGBS appears smooth and contains some spherical particles. These characteristics give it a lower water absorption rate and excellent lubrication, thereby enhancing the fluidity of the grouting material and helping to shorten the flow time. Therefore, see Figure 3 , at a fixed water-solid ratio, the increase in CFB ash content will reduce the free water content in the slurry, thereby extending the flow time. In addition, when the CFB ash content remains consistent, the fluidity of the grouting material will gradually decrease with the increase of the water-solid ratio. This is because the increase in water has the effect of reducing viscosity and diluting, effectively reducing the friction resistance when the slurry flows, thereby shortening the flow time. Therefore, Comparative Examples 1, 2, 3, 5, 8, and 9 do not meet the fluidity requirements.
[0111] Figure 4 It is a comparison chart of the initial setting time of grouting materials prepared with different water-solid ratios at different CFB ash content, which mainly illustrates the effects of CFB ash, GGBS and water-solid ratio on the initial setting time.
[0112] Figure 4In the study, with the increase of CFB ash content, the setting time of the slurry showed an upward trend, which indicates that CFB ash has a certain retarding effect. In the grouting repair of highway subgrade, the "Technical Specifications for Reinforcement of Highway Subgrade and Base Polymer Slurry" (SZ-G-B04-2007) has clear requirements for the setting time of geopolymer grouting materials. The initial setting time shall not be earlier than 30 minutes, and the final setting time shall not be later than 400 minutes. All schemes in this study meet the setting time requirements in the specification. In order to further optimize the repair effect of highway subgrade diseases, it is hoped that the final setting time will be shortened as much as possible while meeting the requirements of the specification. With the increase of CFB ash content, the setting time of the slurry gradually increases. This phenomenon can be attributed to the fact that CFB ash has a larger particle size and smaller specific surface area than GGBS, so its reaction activity is lower, resulting in an increase in setting time. In addition, although CFB ash contains a large amount of Al without high-temperature calcination treatment, it 2 O 3 、SiO 2 and CaO, but their activity is low, so increasing the content of CFB ash will lead to low-activity Al 2 O 3 、SiO 2 The ratio of water content to CaO increases, which in turn affects the reaction rate, thereby extending the setting time. In addition, when the CFB ash content is constant, the setting time of the slurry will increase accordingly with the increase of the water-to-solid ratio. This is because the increased water content reduces the concentration of highly active components in the slurry, delays the progress of the geopolymerization reaction, and thus leads to an extension of the setting time.
[0113] Figure 5 This is a comparison chart of the final setting time of grouting materials prepared at different water-solid ratios at different CFB ash content. It mainly explains the effects of CFB ash, GGBS and water-solid ratio on the final setting time. As mentioned in the above paragraph, with the increase of CFB ash content, the final setting time of the slurry gradually increases. When the CFB ash content is constant, with the increase of water-solid ratio, the final setting time of the slurry will also increase accordingly.
[0114] Figure 6 This is a comparison chart of the water separation rate of grouting materials prepared with different water-solid ratios at different CFB ash dosages. It mainly explains the effects of CFB ash, GGBS and water-solid ratio on the water separation rate.
[0115] The water shedding rate has a profound impact on the grouting repair effect. Excessive water shedding rate will cause the filled voids to form again, especially under the action of vehicle load and water, which is easy to cause roadbed diseases, thus affecting the repair effect. With the increase of CFB ash content, the water shedding rate of the slurry is significantly reduced. This is mainly due to the microscopic surface roughness and pore structure of CFB ash, which enables it to effectively absorb water in the slurry, thereby reducing the water shedding rate. In addition, when the CFB content is constant, the water shedding rate of the slurry will increase accordingly with the increase of water-solid ratio. This increase is particularly significant when the CFB ash content is low, because the increased moisture leads to an increase in the free water content in the slurry, which in turn increases the water shedding rate. In contrast, the porous microstructure of CFB ash makes the slurry consume less water when the CFB content is low. When the free water content increases, the excess water is more likely to precipitate, further leading to an increase in the water shedding rate. Therefore, by adjusting the CFB ash content and water-to-solid ratio when preparing grouting materials, the water separation rate of the slurry can be effectively controlled, thereby optimizing the grouting repair effect and ensuring that the filling material can be stably filled and solidified in the roadbed during actual use, reducing the risk of recurrence of roadbed diseases.
[0116] Figure 7 This is a comparison chart of the 3D compressive strength of grouting materials prepared with different water-solid ratios and different CFB ash content. Figure 8 This is a comparison chart of the 7d compressive strength of grouting materials prepared with different water-solid ratios and different CFB ash content. Fig. 9 This is a comparison chart of the 28d compressive strength of grouting materials prepared with different water-solid ratios and different CFB ash content. It mainly explains the effects of CFB ash, GGBS and water-solid ratio on strength.
[0117] exist Figure 7-Figure 9In this study, the influence of CFB ash content on the compressive strength of the samples was investigated. It was found that the compressive strength of the specimens decreased significantly with the increase of CFB ash content. The main reasons for this phenomenon can be attributed to two aspects. First, CFB ash has low reaction activity due to its low formation temperature; second, CFB ash has a large particle size that is not conducive to the progress of geopolymerization reaction. The combined effect of these two factors led to a significant decrease in the compressive strength of the samples after increasing the CFB ash content. At the same time, the effect of water-solid ratio on the compressive strength of the samples was more significant. With the increase of water-solid ratio, the compressive strength of the samples also decreased significantly. This is because the increased water content diluted the reactive silica and alumina, and also diluted the alkali activator, resulting in a decrease in the amount of gelled products formed in the samples. Therefore, from a macroscopic point of view, these factors jointly led to a significant decrease in the compressive strength of the samples. Although increasing the water-solid ratio can improve the fluidity of the grouting material, its negative impact on the strength cannot be ignored. Comprehensive consideration of the composition ratio and performance requirements of the grouting material is the key to preparing high-performance grouting materials. The comparison in the figure shows that the effect of age on the strength of the samples is not significant. This is because the high calcium oxide content in CFB ash and GGBS improves the early strength. As the age increases, the precursor material and the alkali activator react more thoroughly, resulting in a slight increase in the strength of the samples. According to the requirements of the "Technical Specifications for Geopolymer Grouting Reinforcement of Highway Roadbed and Base" (SZ-G-B04-2007), Examples 4, 6, 7, 10, and 11 do not meet the 7d strength requirements; Examples 7, 10, and 11 do not meet the 28d strength requirements.
[0118] Fig.10 It is the effect of CFB ash content on the expansion rate, which shows that the expansion rate is affected by the water-solid ratio and CFB ash content.
[0119] Fig.10 The influence of CFB ash content on the expansion rate of grouting material samples is shown. It is observed that with the increase of CFB ash content, the expansion rate of the sample increases first and then decreases. This phenomenon is mainly due to the fact that CFB ash contains a certain amount of f-CaO and SO 3 , and GGBS also contains a small amount of SO 3 In an alkaline environment, f-CaO reacts with water to generate Ca(OH) 2 (See formula (1)), SO 3 It will react with active Al 2 O 3 and f-CaO to form calcium vanadium (Ca 6 Al 2 (SO 4 ) 3 (OH)·12H 2 O) (see equation (2)). These reactions will lead to volume expansion. As the amount of CFB ash increases, f-CaO and SO3 The content of Ca(OH) increases, thus generating 2 and calcium vanadium also increased, resulting in an increase in the expansion rate of the sample. However, when the CFB ash content increased further, the generated Ca(OH) 2 When a certain amount is reached, it will react with the active SiO 2 The reaction generates CSH gelling material (see formula (3)), which consumes calcium hydroxide and leads to a decrease in expansion rate. At the same time, when the CFB ash content is further increased, although SO 3 The content increased, but due to the active Al 2 O 3 As the content decreases, the amount of calcium vanadium produced decreases, which ultimately leads to a decrease in the expansion rate. In addition, when the dosage is constant, the expansion rate gradually decreases with the increase of water-to-solid ratio. This is because the increase in water content will reduce the f-CaO and SO 3 , Active SiO 2 and active Al 2 O 3 concentration, thereby weakening the reaction process and resulting in a decrease in the expansion rate.
[0120] f-CaO+H 2 O→Ca(OH) 2 (1)
[0121] CaSO 4 (SO 3 )+Al 2 O 3 +f-CaO+H 2 O→Ca 6 Al 2 (SO 4 ) 3 (OH) 12 ·26H 2 O (2)
[0122] Ca(OH) 2 +SiO 2 +H 2 O→CSH(gel) (3)
[0123] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing ultra-early strength micro-expansion roadbed grouting material using CFB ash, characterized in that: The following steps are involved: S1: Screening CFB ash and blast furnace slag that meet the requirements of particle size and unstable component content; S2: prepare alkali activator; S3: Take CFB ash and blast furnace slag, stir the CFB ash and blast furnace slag, add alkali activator, water reducing agent and water to form grouting material.
2. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 1, characterized in that: In S1, The particle size requirements of CFB ash are: median particle size D 50 ≤70μm.
3. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 1, characterized in that: In S1, The particle size requirements of blast furnace slag are: median particle size D 50 ≤12μm.
4. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 1, characterized in that: In S1, In CFB ash, the unstable components are f-CaO and SO3; The mass percentage of f-CaO is controlled at 1% to 4%, and the mass percentage of SO3 is controlled at 2.5% to 4.5%.
5. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 1, characterized in that: In S2, Use water glass to prepare the alkali activator; The modulus range of water glass is 1.1M~2.2M.
6. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 5, characterized in that: In S2, The modulus of the alkali activator is controlled at 0.9M~1.1M.
7. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 1, characterized in that: In S3, The mass fraction of CFB ash is 60-75 parts, the mass fraction of blast furnace slag is 25-40 parts, the mass fraction of alkali activator is 30-40 parts, the mass fraction of water reducer is 1-2 parts, and the water-solid ratio is 0.63-0.
75.
8. The method for preparing ultra-early strength micro-expansion roadbed grouting material with CFB ash according to claim 7, characterized in that: In S3, When 60 parts ≤ CFB ash parts ≤ 65 parts, the water-solid ratio is controlled at 0.63-0.75; When 65 parts < CFB ash content ≤ 70 parts, the water-solid ratio is controlled at 0.63-0.70; When 70 parts < CFB ash content ≤ 75 parts, the water-solid ratio is controlled at 0.65-0.68.
Citation Information
Cited By
Method for preparing super-ductile prestressed filling material from modified CFB fly ash and application thereof
CN122831648A